2019
DOI: 10.1080/23312009.2019.1565623
|View full text |Cite
|
Sign up to set email alerts
|

Calibration development for nutritional evaluation of Yam (Dioscorea sp.) using Near-Infrared Reflectance Spectrophotometry (NIRS)

Abstract: time. This will enhance breeders' rapid selection of genotypes at screening stage where many breeding lines are to be evaluated within the shortest time possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Near‐infrared spectroscopy calibration models have been developed for rapid and reliable assessment of food quality attributes in various Dioscorea spp. (Alamu, Adesokan, & Maziya‐Dixon, ; Ehounou et al, ; Lebot & Malapa, ; Zhuang, Ni, & Kokot, ). Equations of NIRS calibration with high r 2 values (>.84) for prediction of starch, sugars and proteins (equivalent N) in various Dioscorea spp.…”
Section: High‐throughput Phenotyping In Yammentioning
confidence: 99%
See 1 more Smart Citation
“…Near‐infrared spectroscopy calibration models have been developed for rapid and reliable assessment of food quality attributes in various Dioscorea spp. (Alamu, Adesokan, & Maziya‐Dixon, ; Ehounou et al, ; Lebot & Malapa, ; Zhuang, Ni, & Kokot, ). Equations of NIRS calibration with high r 2 values (>.84) for prediction of starch, sugars and proteins (equivalent N) in various Dioscorea spp.…”
Section: High‐throughput Phenotyping In Yammentioning
confidence: 99%
“…have been developed (Lebot & Malapa, ). Alamu et al () developed NIRS calibration model for prediction of moisture, ash, protein, crude fibre and tannin content in dry tuber samples (flour) of diverse D. rotundata breeding lines with high coefficient of determination values ( r 2 > .80) for the calibration curve and medium to high r 2 values in cross‐validation ( r 2 = .50 for tannin to .80 for moisture content). Ehounou et al () also demonstrated the feasibility of NIRS to predict physicochemical (dry matter content, starches, sugars and proteins) and textural characteristics (hardness, springiness, adhesiveness) on a panel of contrasting D. alata accessions.…”
Section: High‐throughput Phenotyping In Yammentioning
confidence: 99%
“…The analyzer's open-faced sample dish filled with cassava flour was placed in the NIR analyzer scanned by infrared rays, results obtained were displayed on the computer screen. The NIR analyzer was previously standardized by a selection of calibration and validation samples, and reference data obtained by routine laboratory analysis according to the modified method of Alamu et al [21] Modification was the use of cassava flour samples for standardization.…”
Section: Color Properties Of M Esculenta Parenchyma and Flourmentioning
confidence: 99%
“…The samples were scanned by infrared rays emitted by the machine, and the software on the PC displayed the readings obtained. The NIR analyser was previously standardised by a selection of calibration and validation samples and reference data obtained by routine laboratory analysis [ 21 ].…”
Section: Methodsmentioning
confidence: 99%